Na escrita do professor, um percurso possível para a análise do (seu) desenvolvimento profissional - Carnin, Anderson (Universidade do Vale do Rio dos Sinos, 2015)
This research, which was based on a conception of teaching as a work activity (MACHADO, 2004), focused on teachers’ writing practice in a continued studies training and its relation with their professional development. Aiming at broadening the comprehension about how professional writing can mediate the development, a longitudinal qualitative research was conducted. In this research, a dyad of teachers of Portuguese as a mother language was analyzed during a process of continued studies teacher training, taking the concept of textual genre as the articulatory axe of the investigation. In the frame of a cooperative teacher training, in which researchers and teachers are invoiced and have the possibility to change the course of the research (GUIMARÃES; CARNIN, 2014), the development of the notion of textual genre was searched, concerning not only the epistemological perspective but also the praxiological. Enlightened by the theoretical approach of the Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2011, 2013), this study intended to elucidate means of: a) comprehend the teacher’s work writing inserted in the former’s professional environment; b) describe the means in which writing mediates professional knowledge construction by teachers in continued studies training; and c) analyze if there are textual/linguistic traits, highlighted in the teacher’s writing, which allow a visualization of a relationship between professional development and the transformation of the text genre concept in psychological instrument. The analytical exercise took place from two texts produced by the participant teachers who collaborated in the research: genre didactic project (GUIMARÃES; KERSCH, 2012b) and a scientific paper. Considering the linguistic-discursive perspective, the text’s general infrastructure (global plan, thematic contents, discourse types and sequences) and enunciator mechanisms (voices and personal indexes) were analyzed. Aspects related to the psychological dimension of the development were also taken into account, from Bronckart (2011) and Friedrich (2012). Results include (a) the confirmation that teacher’s writing is a powerful instrument for awareness and reconfiguration of the representation of the concept of textual genre; (b) the presentation of a textual/linguistic and discursive analysis which describes the (re)configuration of the concept of textual genre and its transformation into psychological instrument; (c) the discussion about teachers’ writing as the episteme of a teaching practice guided by and to knowledge production in a work situation and (d) the opening of a space of research about the relationship among writing, authorship and professional development.
Keywords: Desenvolvimento profissional; Escrita; Trabalho docente; Formação continuada; Interacionismo sociodiscursivo; Professional/teaching writing; Teaching work; Continued studies training; Professional development; Sociodiscursive interactionism; ACCNPQ::Lingüística, Letras e Artes::Lingüística